Self : a multidisciplinary concept - Dicke, Theresa; Guay, Frédéric; Marsh, Herbert W.; Craven, Rhonda G.; McInerney, D. M. 1948- (International advances in self research., 2020)
"Research on the self relates to various phenomena including self-esteem, self-concept, self-verification, self-awareness, identity, self-efficacy, passion, self-determination, and goals. Moreover, research on self is multidisciplinary and of interest to a broad range of areas, such as education, economics, (social) psychology, neuro sciences, motivation, physical activity and behavior sciences, philosophy, and learning sciences. Chapters in this volume will illustrate some of the best of the research within these disciplines examining different aspects of self from various perspectives. A feature of this volume is that we will explore not only positive aspects of high perceived levels of self-determination and competence or self-concept on achievement, motivation and wellbeing, but also the dark side of an uncertain and negative self on identity and wellbeing. We learn from this that the self is a dynamic and powerful, yet fragile and highly amenable construct that needs self-care and constant reassurance. SELF - A Multidisciplinary Concept thus highlights the broad application of self-research and its diversity. This volume is intended to develop both theoretical and methodological ideas and to present empirical evidence of various disciplines and applications dealing with self. The scope of this seventh volume of the "International advances in self research" series, started in 2000 by Herbert W. Marsh, Dennis M. McInerney, and Rhonda G. Craven, is thus very broad. Keeping within the tradition of the series, this volume will highlight the applicability of a multitude of empirical approaches and methods to self-research. We also aimed to maintain a balance between discussing theoretical research in SELF and deriving implications for effective practice. This volume thus includes chapters covering self-related topics within an educational, social, emotional, psychological, physiological, managerial, and health context"--